Pension Reform Disabled - Sigurd Mølster Galaasen (Norges Bank, 2017)
Old-age pension reform is on the agenda across the OECD, and a key target is to delay retirement. Most of these countries also have a disability insurance (DI) program accounting for a large share of labor force exits. This paper builds a quantitative life-cycle model with endogenous retirement to study how DI and old-age pension (OA-pension) systems interact with health and wages to determine retirement age, with particular focus on the macroeconomic effects of OA-pension reforms. Individuals face uncertain future health status and wages, and if in bad health they are eligible for DI if they choose to retire before reaching the statutory retirement age. I calibrate the model to the Norwegian economy and explore the effects of raising the statutory retirement age and cutting OA-pension on labor supply and public finances. The main contribution of the paper is that I, in contrast to standard macro pension models, include DI as another endogenous margin of retirement. I show that failure to account for this margin might severely bias the analysis of OA-pension reforms.
hdl:11250/2495548
Keywords: E2; E6; H31; H55; J26; 330; retirement; disability insurance; life-cycle; life-cycle